Multidimensional analysis of the Fishery Production System of Mangrove Crab, Ucides cordatus, in Araioses, Maranhão State, Brazil - Cavalcante, Adriana N.; Almeida, Zafira S.; Paz, Alexsandra C.; Nahum, Victoria J. Isaac (Arquivos de Ciências do Mar, 2011)
xThis paper aims to ensure sustainability of the mangrove crab, Ucides cordatus, and to understand the multidisciplinarity involving its production system in the crab-fishing village of Araioses, Maranhão State. The methodology of “case study” has been used with the aid of questionnaires and interviews with the main actors involved in the system, were 11 social actors, seven social processes and 17 components have been identified. The main conflicts result of poor performance of class representatives. Capture of the mangrove crab is mostly through the hand-picking technique. Most families have this activity as the only source of income. The educational level is low. The monthly income obtained varies from R$ 250.00 to R$ 500.00 for collectors and from R$ 250.00 to R$ 1,000.00 for marketers. The sale is made as fresh and technogically-processed products. The fishermen showed great knowledge as to the ecobiology and environmental awareness. The unemployment wage is not compatible with the mangrove crab’s closed-season, although it has been set up for the fishing area and management is already under way in the villages. It is thus observed the need to establish agreements between the social actors of the system and the government offices aiming at improving the living conditions of the human population and the resource management.